Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1634/theoncologist.2015-0111
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of Type 2 Diabetes Mellitus on Early Cervical Cancer in Asia

Abstract: Background. Many studies have shown that type 2 diabetes mellitus (DM) increases the risk for several types of cancer but not cervical cancer (CC). Although DM and insulin‐like growth factor 1 have preclinical and clinical implications for CC, less is known about the prognostic impact of DM on patients with early stage CC. Patients and Methods. We used the nationwide Taiwan Cancer Registry database to collect the characteristics of stage I–IIA cervical cancer patients diagnosed between 2004 and 2008. DM and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
(20 reference statements)
3
9
0
Order By: Relevance
“…Furthermore, we found that early stage cervical cancer patients with type 2 DM had a decreased OS after controlling for comorbid conditions such as obesity and other clinicopathological factors. These results concur with an earlier study [ 15 19 ]. Similarly, Shah et al [ 8 ] evaluated the impact of DM on progression-free survival (PFS) and OS in 367 women with epithelial ovarian cancer.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Furthermore, we found that early stage cervical cancer patients with type 2 DM had a decreased OS after controlling for comorbid conditions such as obesity and other clinicopathological factors. These results concur with an earlier study [ 15 19 ]. Similarly, Shah et al [ 8 ] evaluated the impact of DM on progression-free survival (PFS) and OS in 367 women with epithelial ovarian cancer.…”
Section: Discussionsupporting
confidence: 94%
“…We also found that there was no significant difference between patients with and without type 2 DM in FIGO stage, tumor size, histology, DSI, PI, node status, surgical margin or adjuvant treatment. However, our study did find that patients with type 2 DM were more likely to be older and overweight, which is comparable to previous studies [ 7 9 19 ]. These findings may be explained by the fact that the majority of patients with type 2 DM are obese.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding the impact of T2D on patients who already have CC, it has been suggested that T2D may increase the risk of cancer recurrence and death for early stage CC patients, even after curative treatments. Thus, incorporating T2D screening should be considered as part of the continuum of care for early stage CC patients, and close surveillance during routine follow-up in this population should be recommended [94].…”
Section: T2d and Cervical Cancer (Cc)mentioning
confidence: 99%